Organisational citizenship behaviour and service delivery in urban local governments in Uganda - Wilberforce Turyasingura; Lazarus Nabaho (Commonwealth Journal of Local Governance, 2021)
The quality of service delivery in decentralised local governments (LGs) in Uganda remains largely unsatisfactory, despite central government’s efforts to improve resource allocation and develop supporting legal frameworks. This has been partly linked to the extent to which LG staff exhibit ‘organisational citizenship behaviour’ (OCB). Extant literature has not given adequate attention to OCB in the decentralisation discourse, especially in sub-national governments within developing countries such as Uganda. This paper tackles the issue of OCB among LG employees and its relationship to service delivery by addressing the following questions: (a) what is the level of OCB among LG employees and (b) to what extent do various dimensions of OCB relate to the quality of service delivery in the decentralised LG context?